Enhancing the Capacity and Quality of Wader Fish Production Using Wader Drying Ovens in Sidoarjo: Peningkatan Kapasitas dan Kualitas Produksi Wader dengan Oven Pengering Wader di Sidoarjo - Fitra Mardiana; M. Hasan Abdullah; Wahyu Nugroho (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The market demand for dried fish requires the application of technology to ensure a steady supply. This Community Partnership Program aims to enhance the capacity and quality of wader fish production using wader drying ovens in Sidoarjo. This initiative addresses three key issues faced by wader fish producers: reliance on traditional equipment for production, unstable sales, lack of processed food labeling permits, and the use of plastic trays with inadequate packaging that is not tightly sealed. The activities include the development of appropriate technology (TTG), training, and mentoring. The program outcomes include the provision of wader drying TTG equipment, deep frying tools, halal certification processing, procurement of trays and sealing machines (induction magnetic sealers), as well as training and mentoring utilizing social media platforms and marketplaces. The results are expected to significantly enhance the partners' business operations in the long term.